2013
DOI: 10.5539/jas.v5n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Effects for Yield and Yield Components in Chickpea (Cicer arietinum L.) under Irrigated and Rainfed Conditions

Abstract: Seven genetically diverse parents of chickpea were crossed in five combinations (RSG-895 x RSG-888, RSG-888 x ICC-4958, IPC-94-94 x RSG-888, CSJD-901 x RSG-931 and BG-362 x RSG-931) to develop F 1 , F 2 and F 3 hybrid progenies. Five generations viz., P 1 , P 2 , F 1 , F 2 and F 3 were grown in a compact family block design under irrigated and rainfed conditions to estimate the gene effects for yield and yield components. Scaling test 'C' and 'D' as well as joint scaling test revealed presence of epistatic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
3
6
0
Order By: Relevance
“…Since, additive and non-additive gene action were important for this trait, improvement may be possible by delaying selection to later filial generations. These findings are in agreement with Kumhar et al (2013).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Since, additive and non-additive gene action were important for this trait, improvement may be possible by delaying selection to later filial generations. These findings are in agreement with Kumhar et al (2013).…”
Section: Discussionsupporting
confidence: 92%
“…Preponderance of additive effect, additive 9 additive interaction, along with complementary type of interaction showed effectiveness of selection for improving this trait. Similar results were observed by Bhardwaj and Sandhu (2007) and Kumhar et al (2013) in chickpea.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It has also been considered as an important factor for subsequent plant growth parameters including germination, seedling vigour and seedling mass (Narayanan et al 1981;Dahiya et al 1985). Earlier studies have reported monogenic (Argikar 1956), digenic (Ghatge 1993;Upadhyaya et al 2006;Hossain et al 2010), oligogenic (Patil and D'Cruze 1964) and polygenic (Niknejad et al 1971;Kumar and Singh 1995;Malhotra et al 1997;Kumhar et al 2013) inheritance of seed size depending on the number of genes segregating in the populations studied. According to Smithson et al (1985) and Kumar and Singh (1995), small seed size was dominant over large one.…”
Section: Introductionmentioning
confidence: 93%